The interplay of TGF-β1 and cholesterol orchestrating hepatocyte cell fate, EMT, and signals for HSC activation - Wang, Sai; Link, Frederik; Han, Mei; Chaudhary, Roohi; Asimakopoulos, Anastasia; Liebe, Roman; Yao, Ye; Hammad, Seddik; Dropmann, Anne; Krizanac, Marinela; Rubie, Claudia; Feiner, Laura Kim; et al. (Cellular and Molecular Gastroenterology and Hepatology, 2024)
Background & Aims - Transforming growth factor-β1 (TGF-β1) plays important roles in chronic liver diseases, including metabolic dysfunction-associated steatotic liver disease (MASLD). MASLD involves various biological processes including dysfunctional cholesterol metabolism and contributes to progression to metabolic dysfunction-associated steatohepatitis and hepatocellular carcinoma. However, the reciprocal regulation of TGF-β1 signaling and cholesterol metabolism in MASLD is yet unknown. - Methods - Changes in transcription of genes associated with cholesterol metabolism were assessed by RNA sequencing of murine hepatocyte cell line (alpha mouse liver 12/AML12) and mouse primary hepatocytes treated with TGF-β1. Functional assays were performed on AML12 cells (untreated, TGF-β1 treated, or subjected to cholesterol enrichment [CE] or cholesterol depletion [CD]), and on mice injected with adenovirus-associated virus 8-control/TGF-β1. - Results - TGF-β1 inhibited messenger RNA expression of several cholesterol metabolism regulatory genes, including rate-limiting enzymes of cholesterol biosynthesis in AML12 cells, mouse primary hepatocytes, and adenovirus-associated virus-TGF-β1-treated mice. Total cholesterol levels and lipid droplet accumulation in AML12 cells and liver tissue also were reduced upon TGF-β1 treatment. Smad2/3 phosphorylation after 2 hours of TGF-β1 treatment persisted after CE or CD and was mildly increased after CD, whereas TGF-β1-mediated AKT phosphorylation (30 min) was inhibited by CE. Furthermore, CE protected AML12 cells from several effects mediated by 72 hours of incubation with TGF-β1, including epithelial-mesenchymal transition, actin polymerization, and apoptosis. CD mimicked the outcome of long-term TGF-β1 administration, an effect that was blocked by an inhibitor of the type I TGF-β receptor. In addition, the supernatant of CE- or CD-treated AML12 cells inhibited or promoted, respectively, the activation of LX-2 hepatic stellate cells. - Conclusions - TGF-β1 inhibits cholesterol metabolism whereas cholesterol attenuates TGF-β1 downstream effects in hepatocytes.